CONVERSATION ANALYSIS : A REPORT ON MINI RESEARCH - Sitti Nurfaidah (Institut Agama Islam Negeri (IAIN) Kendari, 2015)
This article demonstrates several aspects of the conversation analytic approach asrevealed from the transcribed data. Through Conversation Analysis (CA), it isrevealed that preference organization, another aspect of sequence organization,does occur in the communication. Moreover, CA shows the constitution of themeaning of utterances through sequential reasoning. CA also illustrates that themethods by which participants make sense of their talk may be (re-)specified and(re-)negotiated in the course of interaction.Keywords: conversation analysis, turn-taking, adjacency pairs, preferred response,dispreferred response